METTL3-modified lncRNA-MALAT1 regulates the molecular axis of miR-124-3p/CDK4 involved in Ewing's sarcoma: Study on the Mechanism of METTL3 in Ewing's Sarcoma - He, Fangzhou; Ren, Tingting; Tang, Xiaodong (Cellular and Molecular Biology, 2023)
N6-methyladenosine (m6A) modifications are considered key mechanisms in cancer. As an m6A-modified lncRNA, MALAT1 is associated with tumor progression. In this study, the MALAT1/miR-124-3p/CDK4 axis was studied to discover METTL3’s effects on Ewing's sarcoma (ES). For this purpose, clinical ES samples were collected and ES cells were cultured to detect gene expression. Then, the interlink between METTL3, MALAT1, miR-124-3p, and CDK4 was studied and confirmed, and m6A modification of MALAT1 was determined. Finally, the Transwell method was used to test migration and invasion. Results showed that ES samples expressed low miR-124-3p and high METTL3, MALAT1 and CDK4. METTL3 elevated MALAT1 expression by m6A modification. MALAT1 enhanced CDK4 expression by competing with miR-124-3p. In ES cells, METTL3 silencing repressed cell migration and invasion by inhibiting MALAT1. In conclusion, METTL3 promotes tumorigenesis of ES through the MALAT1/miR-124-3p/CDK4 axis.